Mitophagy: A Potential Therapeutic Target for Tuberculosis Immunotherapy - Gao S (ImmunoTargets and Therapy, 2025)
Siyu Gao,1,* Zeliang Yang,1,* Jiajia Yu,2 Fuzhen Zhang,1,3 Shenjie Tang,4 Yu Pang1 1Department of Bacteriology and Immunology, Beijing Chest Hospital, Capital Medical University/Beijing Tuberculosis & Thoracic Tumor Research Institute, Beijing, 101149, People’s Republic of China; 2Department of Infectious Diseases and Clinical Microbiology, Beijing Chaoyang Hospital, Capital Medical University, Beijing, 100020, People’s Republic of China; 3Department of Epidemiology, School of Public Health, Cheeloo College of Medicine, Shandong University, Jinan, 250012, People’s Republic of China; 4Clinical Center on Tuberculosis, Beijing Chest Hospital, Capital Medical University/Beijing Tuberculosis & Thoracic Tumor Research Institute, Beijing, 101149, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yu Pang, Department of Bacteriology and Immunology, Beijing Chest Hospital, Capital Medical University/Beijing Tuberculosis & Thoracic Tumor Research Institute, No. 9 Beiguan Street, Tongzhou District, Beijing, 101149, People’s Republic of China, Tel +86 13810098209, Email pangyupound@163.com Shenjie Tang, Clinical Center on Tuberculosis, Beijing Chest Hospital, Capital Medical University/Beijing Tuberculosis & Thoracic Tumor Research Institute, No. 9 Beiguan Street, Tongzhou District, Beijing, 101149, People’s Republic of China, Tel +86 13621028338, Email tangsj1106@vip.sina.comAbstract: Mitophagy serves as a cytoprotective mechanism that is essential for eliminating dysfunctional or superfluous mitochondria, thereby fine-tuning mitochondrial quantity and maintaining cellular homeostasis. Recent studies underscore the critical role of mitophagy in determining the fate and function of host cells infected by Mycobacterium tuberculosis. The successful pathogen strategically integrates into the host’s mitochondrial network, manipulating processes such as apoptosis, metabolic reprogramming, mitochondrial fusion and fission, and reactive oxygen species production. Therefore, understanding those mechanisms is critical for the advancements of host-directed therapies against tuberculosis. This study offers a comprehensive overview of the interplay between Mycobacterium tuberculosis and mitophagy, emphasizing the associated signaling pathways and potential therapeutic targets involved in mitophagy in Mycobacterium tuberculosis infection. Activating mitophagy in infected host cells represents a promising avenue for improving therapeutic outcomes against tuberculosis. This review aims to summarize potential research direction for agents targeting induction of mitophagy. Notably, evidence suggests that BNIP3/NIX-mediated mitophagy may serve as a potential therapeutic target.Keywords: mitophagy, Mycobacterium tuberculosis, tuberculosis, immunotherapy